The Role of Product Attributes and Price to Purchase Intentions for Oleh-Oleh Sago Tumbu - Pattipeilohy, Victor Ringhard; Gommies, Stevanus Johan; Pattipeilohy, Vascolino (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2024)
The study examines the impact of product attributes and pricing on consumer purchase intentions for sago tumbu, a traditional Maluku snack. It employs a quantitative approach with explanatory research design, focusing on the relationship between independent variables (product attributes and price) and the dependent variable (purchase intentions). Data from 120 respondents, patrons of specialty snack outlets in Ambon City, were collected using a 5-point Likert scale and analyzed through multiple regression analysis using SPSS 23. The findings highlight the significant positive influence of both product attributes and pricing on consumer purchase intentions. Recommendations include enhancing product packaging and labeling attractiveness while maintaining affordable pricing to stimulate consumer purchasing intentions.